Influence of mean stress on the fatigue strength of ASTM A743 CA6NM alloy steel - José Alexander Araújo; Felipe Oliveira; Jorge Luiz de Almeida Ferreira; Braitner Lobato da Silva (Fracture and Structural Integrity)
The objective of this work is to evaluate the effects of mean stress on the fatigue behavior of ASTM A743 CA6NM alloy steel. It is used in several hydrogenator turbine components. In order to achieve it, 33 specimens were experimentally evaluated under axial loads with stress ratio of - 1 and more 60 specimens were tested under stress ratio 0, 1/3 and 2/3. Based on the obtained results it was possible to determine parameters that describe the fatigue behavior of the evaluated material, obtain its S-N curves, its endurance limit and its scatter bands. In the assessment of the mean stress effects of fatigue life, Goodman, Gerber, Walker and Kwofie’s relations were tested in order to evaluate the validity of the use of such rules for the tested material. According to the obtained results it was possible to verify that Goodman and Gerber’s relations do not model correctly the reduction effect fatigue life and presented high scatter. The predictions of Walker and Kwofie’s relation are consistent and the Walker’s relation presented smaller scatter than Kwofie’s relation. Walker’s relation makes it possible to evaluate in a consistent way the effect of the presence of mean stresses on fatigue strength.